Nutritional Status of the Elderly Population Having Dental Problem in the Selected Community - Gaire, Bipula; Shakya, Manodhara; Lama, Monika (Journal of Karnali Academy of Health Sciences, 2020)
Background: Good nutrition is the foundation for a healthy life. Malnutrition is associated with higher rates of morbidity and mortality as well as increased health care expenditures, and prolonged hospital stays. Elderly People are uniquely susceptible to malnutrition due to the association of aging with various factors that influence nutritional status. Dental Problems in elderly can cause difficulty with chewing food and swallowing, leading to a decrease in nutrient intake affecting nutritional status. Thus, the objective of the study was to assess the nutritional status of the elderly population having a dental problem in Harisiddhi, Lalitpur, Nepal. Methodology: A community-based cross-sectional descriptive study was undertaken at, Harisiddhi, Lalitpur with one hundred fifty (N=150) elderly people by using a systematic random sampling method. The MiniNutritional Assessment – Short Form tool was utilized for interviewing elderly people.Results: The main findings of this study revealed that 60% of the elderly people having dental problems were at risk of malnutrition, only 22% had normal nutritional status and 18% of the respondents were malnourished. The average Body Mass Index of elderly people was 27.1 kg/m2. There was a significant association between age, educational status, types of family, income source, type of dental problem, and nutritional status of the respondents.Conclusions: More than half of the elderly people having dental problem are at risk of malnutrition and only a few have normal nutritional status so nutritional counselling and dental health program should be conducted among the elderly people focusing on the importance of balanced diet, activity and dental health for maintaining the nutritional status within their motivation and energy level.